Scenarios of colonialism and (de) coloniality in the construction of the Black Being. Notes on gender relations in black communities of the Colombian Pacific - Grueso, Libia (2016)
The gender relations in black communities are mediated by the legacy of slavery to which the afro-descendant population in the Americas was submitted; these relations shape the historical construction black-being. Even the patriarchal structure was a jurisdiction of the slave masters, and not of the black man dispossessed of himself through slavery. Both the black man and black woman slaves were commodities, their sexuality and their relations formed part of the mercantile function that the masters infringed on them; motherhood was a profession and the black man a reproductive of goods. This article argues that because of this history the right to Be is the first stage in the organized proposal of PCN –Process of Black Communities–, this understood as a strategy of dignification, it is the recuperation of the dignity of being black a strategy of internal and external decolonization from the subject herself/himself towards and from the surrounding society.